Internalisasi Nilai Spiritual Islam dalam Diseminasi Anti-Rokok di Pesantren - Susi Puspita Sari; Jamal Mirdad; M Amiin; Rina Rina; Wulandari Wulandari; Afriwes Afriwes; Adi Fita Andikos; Rani Safitri (Jurnal Ilmiah Pengabdian Kepada Masyarakat, 2026)
Islamic boarding schools (pondok pesantren) are Islamic educational institutions that play a strategic role in shaping the character and behavior of the younger generation. As centers of civilization, these schools focus not only on intellectual and spiritual development but also on physical health as the foundation for students’ productivity. However, a major challenge arises from the persistently high prevalence of smoking in educational settings, including Islamic boarding schools, which is often viewed as part of a specific social culture The phenomenon of smoking among students contradicts the principles of Hifzu al-Nafs (preserving life) and Hifzu al-Maal (preserving wealth) within the maqashid al-sharia. Exposure to secondhand smoke not only adversely affects respiratory health but has also been empirically proven to reduce students’ concentration levels and memory retention. If left unchecked, this will hinder the pesantren’s vision of producing a productive and competitive “golden generation” for the future. Efforts to prevent smoking have so far often been limited to instructional guidance or top-down administrative bans. In reality, Islamic boarding schools possess a far more powerful tool: Islamic spiritual and moral values. Internalizing these values through a persuasive approach that resonates with the students’ inner selves is believed to foster self-awareness and the will to avoid smoking. Therefore, a comprehensive anti-smoking dissemination strategy is needed. This dissemination should not merely involve sharing medical information but should also integrate religious principles, the leadership of religious figures (Kyai), and the role of peer counselors. Under the title “Internalization of Islamic Spiritual Values in Anti-Smoking Dissemination Campaigns in Islamic Boarding Schools,” this research/activity aims to formulate a smoking prevention model based on the students’ identity, in order to create a healthy, clean boarding school environment that fully supports the students’ productivity in worship and the pursuit of knowledge